A meta-analysis of different HR-enhancing practices and performance of small and medium sized firms - Rauch, Andreas; Hatak, Isabella (Journal of Business Venturing, 2016)
The role of human capital has received considerable attention in research on small and medium sized firms. However, much uncertainty remains as to how practices that enhance human resources (HR) affect the performance of small and medium sized firms, whether some practices have stronger effects than others, and which contingencies influence these effects. Relying on the framework proposed by Subramony (2009), we propose that small and medium sized firms need to implement HR practices that focus on enhancing skills, motivation, and empowerment. The results of our meta-analysis comprising 56 studies that focused on small and medium sized enterprises (SME) indicated that HR-enhancing practices are correlated with firm performance (rc=.228). Moreover, HR-enhancing practices were more relevant for young firms and SME operating in high-tech industries and in country contexts characterized by rigid labor regulations. We compare the results of this meta-analysis with meta-analyses performed in the large firm context. Overall, our results suggest that HR-enhancing practices are important in the SME context in general and, moreover, they specify whether or not these practices have to be adapted to the SME context.